Variation in viscoelastic properties of bovine articular cartilage below, up to and above healthy gait-relevant loading frequencies. (February 2015) - Sadeghi, Hamid; Espino, Daniel M; Shepherd, Duncan ET
The aim of this study was to determine the variation in viscoelastic properties of femoral head bovine articular cartilage, on-bone, over five orders of magnitude of loading frequency. These frequencies ranged from below, up to and above healthy gait-relevant frequencies, using<1, 1–5 and 10 Hz, respectively. Dynamic mechanical analysis was used to measure storage and loss stiffness. A maximum compressive force of 36 N was applied through a chamfered-end, 5.2-mm-diameter, indenter. This induced a maximum nominal stress of 1.7 MPa. The ratio of storage to loss stiffness increased from near parity (2.5) at low frequencies to 11.4 at 10 Hz. This was the result of a significant logarithmic increase ( p < 0.05) in storage stiffness with frequency, from 367 N/mm (0.001 Hz) up to 1460 N/mm (10 Hz). In contrast, the loss stiffness remained approximately constant. In conclusion, viscoelastic properties of articular cartilage measured at frequencies below those of gait activities are poor predictors of its relevant dynamic mechanical behaviour.